Association Between Rates of Caesarean Section and Maternal and Neonatal Mortality in the 21st Century: A Worldwide Population-based Ecological Study With Longitudinal Data. Issue 1 (March 2017) - Ye, J.; Zhang, J.; Mikolajczyk, R.; Torloni, M.R.; G[Euro sign]ulmezoglu, A.M.; Betran, A.P.
Abstract : ( BJOG. 2016;123:745–753) A significant increase in cesarean deliveries has been reported worldwide over the past few decades. Earlier studies analyzed the association between delivery mode and maternal and neonatal mortality using various statistical methods and found a nonlinear relationship between the 2. However, these studies did not control for socioeconomic conditions. The objective of this study was to compile the data available on cesarean section rates worldwide, determine the association between mode of delivery and maternal and neonatal mortality when adjusting for socioeconomic development, and determine a population level cesarean section rate that is associated with the least maternal and neonatal mortality.